The Role of the Physical and Social Environment in Observed and Self-Reported Park Use in Low-Income Neighborhoods in New York City - Javier E. Otero Peña; Javier E. Otero Peña; Hanish Kodali; Emily Ferris; Katarzyna Wyka; Setha Low; Kelly R. Evenson; Joan M. Dorn; Lorna E. Thorpe; Terry T. K. Huang (Frontiers Media S.A., 2021)
Physical and social environments of parks and neighborhoods influence park use, but the extent of their relative influence remains unclear. This cross-sectional study examined the relationship between the physical and social environment of parks and both observed and self-reported park use in low-income neighborhoods in New York City. We conducted community- (n = 54 parks) and individual-level (n = 904 residents) analyses. At the community level, observed park use was measured using a validated park audit tool and regressed on the number of facilities and programmed activities in parks, violent crime, stop-and-frisk incidents, and traffic accidents. At the individual level, self-reported park use was regressed on perceived park quality, crime, traffic-related walkability, park use by others, and social cohesion and trust. Data were collected in 2016-2018 and analyzed in 2019-2020. At the community level, observed park use was negatively associated with stop-and-frisk (β = −0.04; SE = 0.02; p < 0.05) and positively associated with the number of park facilities (β = 1.46; SE = 0.57; p < 0.05) and events (β = 0.16; SE = 0.16; p < 0.01). At the individual level, self-reported park use was positively associated with the social cohesion and trust scale (β = 0.02; SE = 0.01; p < 0.05). These results indicate that physical and social attributes of parks, but not perceptions of parks, were significantly associated with park use. The social environment of neighborhoods at both community and individual levels was significantly related to park use. Policies for increasing park use should focus on improving the social environment of parks and surrounding communities, not only parks' physical attributes. These findings can inform urban planning and public health interventions aimed at improving the well-being of residents in low-income communities.